Microscopic hydration properties of the a beta(1-42) peptide monomer and the globular protein ubiquitin: a comparative molecular dynamics study - Jose, Jaya C.; Khatua, Prabir; Bansal, Nupur; Sengupta, Neelanjana; Bandyopadhyay, Sanjoy (Journal of Physical Chemistry B, 2014)
Atomistic molecular dynamics simulations of eight selected conformations of a disordered protein amyloid beta (1-42) (A beta), and a globular protein, ubiquitin(UBQ), have been carried out in aqueous media at 310 K. Detailed analyses were carried out to compare the microscopic properties of water molecules present in the hydration layers of these systems. It is notices that irrespective of the conformational heterogeneity among the A beta monomers, water molecules hydrating UBQ. Importantly, the conformational heterogeneity of the A beta monomers has been found to affect the translational and rotational motions of hydration water molecules in a nonuniform manner. Detailed investigation of the timescale of hydrogen bond relaxations at the surface and their energetics revealed the possibility of heterogeneous confinement around different A beta conformations. The distribution of water density fluctuation around A beta conformations are broader compared density fluctuation among the A beta monomers suggests that the structural propensities could affect the peptides effective surface hydrophobicity.

Conformational features of the Aβ42 peptide monomer and its interaction with the surrounding solvent - Khatua, Prabir; Jose, Jaya C.; Sengupta, Neelanjana; Bandyopadhyay, Sanjoy (Physical Chemistry Chemical Physics, 2016)